El Procedimiento Expedito y la Violación de Principios Constitucionales en la Apertura de la Prescripción por no Concurrencia del Denunciante en las Contravenciones del Derecho de Propiedad - Alvarado Sánchez, Tania Paola (2018)
The present investigation work called "The Expedited Procedure and the Violation of Constitutional Principles in the Opening of the Prescription for Non-Concurrence of the Complainant in the Contraventions of Property Law", has the purpose of carrying out a critical, legal and doctrinal study of the Organic Code Comprehensive criminal, on the abandonment or filing of the process in expedited procedure of contraventions against the right of property when the victim does not attend the hearing, since I consider that this issue is of great importance within the area of Criminal Law in our country, mainly because Our Constitution protects the rights and guarantees of both the victim and the person prosecuted. In this way, an extensive review of literature has been developed as the conceptual framework where I analyzed clearly and precisely definitions such as: property, principles, prescription, victim, prosecution, expedited procedure, contravention, abandonment, judicial file, concurrence, complaint and right . Once I have obtained and collected basic concepts, I proceeded to carry out a doctrinal study where I took several points of view from different authors related to the subject matter; then a legal study where I analyzed the Constitution of the Republic, the Comprehensive Criminal Code and the Organic Code of the Judicial Function and finally a study of comparative law of Spanish law. 5 I have made the presentation of the results of the field work, through the techniques of the survey and interview aimed at legal professionals giving me necessary and important information to conclude with my projected study, and to be able to demonstrate the objectives and the hypothesis presented in the presented project , based on the results obtained, elaborate the conclusions and recommendations that have been arrived at as a result of the exhaustive and meticulous analysis that has been carried out in the present investigation. Also, the case study of which was a fundamental piece since it helped me determine the violation of rights to the accused and principles such as equality before the law and procedural economy. Finally, for the Legal Basis, I relied mainly on the Constitution of the Republic of Ecuador and the Comprehensive Organic Code, with field research being the fundamental part to be able to conclude with the proposed legal refoeform.